PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS WORD SQUARE PADA MATERI SISTEM ORGANISASI KEHIDUPAN KELAS VII SMP - Nurhidayati Lutvia; Darmawati Darmawati; Mariani Natalina (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract : This study aims to produce LKPD based on word square for quality life organization system material. The first stage is product validation by validators, namely Biology Education lecturers in Biology Education Laboratory, Riau University, and science teachers at SMPN 37 Pekanbaru. The implementation time of this research is May-June 2022. The development model used in this study refers to the Research and development which consists of 5 stages, namely analysis, design, development, implementation, and evaluation. In this study, researchers only carried out until the development stage. The instrument used to collect data is a validation sheet which consists of 3 aspects, namely aspects of content feasibility, design, and pedagogy. Research data was collected by filling out the validation sheet. A validation sheet will be given to the validator to determine the level of validity of the product that has been developed. This analysis technique is done by descriptive analysis. The validity of the LKPD is determined by the average value given by each validator. The results of the validation of the LKPD based on Word Square on the content feasibility aspect are 3.48 with a very valid category, the design aspect of 3.33 with a very valid category, and the pedagogic aspect of 3.56 with a very valid category. The overall average for the three aspects is 3.45 with a very valid category.Key Words : Development, Student Worksheet, Word Square